REKONSTRUKSI OBLIGASI: INVESTASI DALAM PERSPEKTIF SYARIAH - Nurul Fatma Hasan & M. Mujib Utsmani (Qawanin: Jurnal of Economic Syaria Law, 2017)
Investment is highly recommended in Islam. The Al-Quran and Al-Hadith of Prophet Muhammad PBUH and companions support the existence of investment in the use of productive capital resources. The investment must be in accordance with the rules of Islam. Norms in investing according to sharia are free from elements of usury, uncertainty (gharar), gambling (maysir), haram, and syubhat. Bond is one form of investment, but the practice of conventional bonds is usury which is clearly forbidden by the verses of the Qur'an and hadith Saheeh and consensus (ijma ') of the scholars both salaf and khalaf. The reconstruction of bonds to conform to sharia principles needs to take into account some of the underlying prohibitions with bonds. Basically the fundamental difference between sharia bonds and conventional bonds lies in the determination of interest rates of magnitude determined at the beginning of the transaction. Syariah bonds are not a fixed interest-bearing debt as contained in conventional bonds, but rather are fund-raisers based on the principle of profit-sharing. The transaction is not a debt of accounts receivable but an inclusion. Sharia bonds (sukuk) as a form of financing and investment allow some form of structure that can be offered to avoid usury. Sharia bonds can be profit sharing based on mudharabah / muqaradhah / qiradh or musyarakah. While margin / fee based on murabaha or salam or istishna '.